2021
DOI: 10.1158/1078-0432.ccr-20-4476
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of Sipuleucel-T with or without Radium-223 in Men with Bone-metastatic Castration-resistant Prostate Cancer

Abstract: Purpose: To investigate if radium-223 increases peripheral immune responses to sipuleucel-T in men with bone-predominant, minimally symptomatic metastatic castration-resistant prostate cancer (mCRPC).Methods: 32 patients were randomized 1:1 in this open label, phase 2 multicenter trial. Patients in the control arm received 3 sipuleucel-T treatments, 2 weeks apart. Those in the combination arm received 6 doses of radium-223 monthly, with sipuleucel-T intercalated between the second and fourth doses of radium-22… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 18 publications
(24 reference statements)
0
21
0
1
Order By: Relevance
“…This immunosuppression can, however, be due to concomitant dexamethasone treatment [ 191 ]. Radium-223 has also been studied in combination with sipuleucel-T. Interim results of a phase 2 combination study suggest synergistic effects, but further studies are warranted [ 192 ]. In relation to radium-223, monitoring and maintaining bone health are important in prostate cancer patients [ 193 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…This immunosuppression can, however, be due to concomitant dexamethasone treatment [ 191 ]. Radium-223 has also been studied in combination with sipuleucel-T. Interim results of a phase 2 combination study suggest synergistic effects, but further studies are warranted [ 192 ]. In relation to radium-223, monitoring and maintaining bone health are important in prostate cancer patients [ 193 ].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Another phase II trial assessed the combination of sipuleucel-T and a radioisotope, radium-223, in patients with mCRPC. Despite paradoxically decreased the immune response in the combination arm, PSA levels were decreased and PFS and OS longer [204]. A case report by Han et al presents a significant clinical response to pembrolizumab and radiation combination in patient heavily treated mCRPC with rectal involvement.…”
Section: Radiation and Immune Therapy Combinationmentioning
confidence: 99%
“…Table 2 presents a comparison of the immunomodulatory impact of different local therapies on TME. [ 188,192,[201][202][203][204][205][193][194][195][196][197][198][199][200] HIFU: high-intensity focused ultrasound; PDT: photodynamic therapy; IRE: irreversible electroporation; RT: radiotherapy; DC: dendritic cell; CTL: cytotoxic T-lymphocyte; NK: natural killer; IL: interleukin; Treg: regulatory T cell; MDSC: myeloid-derived suppressor cell; APC: antigen-presenting cell; TNF: tumor necrosis factor; MHC: major histocompatibility complex.…”
Section: Radiation and Immune Therapy Combinationmentioning
confidence: 99%
“…A small percentage, 4.8%–2.6% of Sipuleucel‐T‐treated patients showed PSA reductions at least 50% on two visits at least 4 weeks apart, as compared with 1.3%–0% in the placebo group 55,56 . A synergistic effect of the combination of Sipuleucel‐T and Radium‐223 (Ra223) was evaluated in men with asymptomatic bone‐metastatic CRPC in an ongoing phase II clinical trial which has shown much improved PSA reduction (31%, vs. 0% in Sipuleucel‐T only group) and longer progression‐free survival (39 weeks vs. 12 weeks Sipuleucel‐T only group) in combined Sipuleucel‐T/Ra223 treatment group 66 …”
Section: Immunotherapy In Treatment Of Prostate Cancermentioning
confidence: 99%